2023
DOI: 10.3390/polym15041058
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology (RSM) Approach to Optimization of Coagulation-Flocculation of Aquaculture Wastewater Treatment Using Chitosan from Carapace of Giant Freshwater Prawn Macrobrachium rosenbergii

Abstract: The major sources of waste from aquaculture operations emanates from fish or shellfish processing and wastewater generation. A simple technique called coagulation/flocculation utilizes biowaste from aquaculture to produce chitosan coagulant for wastewater treatment. A chemical method was applied in the present study for chitin and chitosan extraction from carapace of Macrobrachium rosenbergii and subsequent application for removal of turbidity and salinity from shrimp aquaculture wastewater. Box-Behnken in RSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 72 publications
0
2
1
Order By: Relevance
“…Luo et al [5] and Kumari et al [7] reported a similar outcome for chitosan extracted from shrimp shells (246%), fish scales (226%), and grasshoppers (275%). However, the FBC values of both forms of extracted chitosan in this study were lower than those of chitosan from mealworm (574%), silkworm chrysalis (412%) [5], black tiger shrimp shells (397-428%) [17], and giant freshwater prawn (372.33%) [27]. The FBC value generally depends on the source of raw material and chitosan production [25].…”
Section: Water-binding Capacity and Fat-binding Capacitycontrasting
confidence: 56%
“…Luo et al [5] and Kumari et al [7] reported a similar outcome for chitosan extracted from shrimp shells (246%), fish scales (226%), and grasshoppers (275%). However, the FBC values of both forms of extracted chitosan in this study were lower than those of chitosan from mealworm (574%), silkworm chrysalis (412%) [5], black tiger shrimp shells (397-428%) [17], and giant freshwater prawn (372.33%) [27]. The FBC value generally depends on the source of raw material and chitosan production [25].…”
Section: Water-binding Capacity and Fat-binding Capacitycontrasting
confidence: 56%
“…A study was conducted to treat aquaculture wastewater using bioflocculant, where the treatment managed to decrease the turbidity by 84% and remove suspended solids by 79% (Kurniawan et al 2022). Another study was conducted using a natural flocculant (chitosan) and was able to remove the turbidity by 87.7% (Iber et al 2023), which falls in the same range as the bioflocculant used in the previous study. However, when using organic poly aluminum chloride, a chemical coagulant, the removal efficiency of turbidity, TSS, and phosphorus was over 97% (Heiderscheidt et al 2020).…”
Section: Coagulation and Flocculationmentioning
confidence: 99%
“…Box-Behnken design (BBD) of the RSM of the Design-Expert 12 software (State-Ease, USA) was utilized to investigate the relationship between the input variables and the output responses, obtain the fitted model, and generate optimal operating conditions of FAS poly-coagulants for algae removal [22,46]. In this study, the three input variables chosen were n(Fe):n(Al), m(Si):m(Al+Fe), and n(CO 3 2− ):n(Al+Fe).…”
Section: Experimental Designmentioning
confidence: 99%